AB0047 Characterisation and Activation of Dendritic Cell Within the Inflammed Synovium of Rheumatoid Arthritis Patients. (9th June 2015) - Canavan, M.; O'Rourke, M.; Orr, C.; Veale, D.; Fearon, U.
Abstract : Background: Dendritic cells (DC) are a heterogeneous population of professional antigen presenting cells which link both innate and adaptive immunity. Myeloid and plasmacytoid DCs represent the two major DC subsets and can be distinguished based on their morphology, expression of surface markers and gene expression profiles. Although DC have previously been identified within the inflamed synovium, the role of these cells and their various subsets has yet to be extensively explored. Objectives: In this study we examined the activation and maturation of DC within the inflamed synovium compared to circulating blood in an effort to understand how the microenvironment within the joint can drive inflammatory DC activation and recruitment. Methods: DC whole blood phenotyping was assessed using multicolour flow cytometry on the Beckman Coulter Cyan system using FlowJo software for subsequent analysis. DC were defined as HLADR +, Lineage -, and further subdivided as either myeloid (CD11c +, CD1c + or CD141 + ) or plasmacytoid DC (CD123 + ). Cell surface expression of CD80, CD83 and CD40 was used to assess the activation and maturation status of each subtype. For characterisation of synovial tissue DC, biopsies were digested using the GentleMACs mechanical and enzymatic digestion system. Viable CD45 cells were gated and subsequently assessed for DC pan markers in addition to maturation and activation markers. In parallel, synovial fluid and peripheral blood were comparatively assessed to profile DC from blood, fluid and tissue. To assess the effect of the synovial environment on DC maturation, immature DC were derived from CD14+ monocytes in the presence of GMCSF (100ng/ml) and IL-4 (70ng/ml). Synovial tissue explants were cultured for 24hr allowing the spontaneous release of cytokines and soluble mediators into the culture medium. MoDC were cultured in the presence of this explant conditioned media for 24hr after which the expression of maturation markers was analysed on CD11c + CD14 - DC. Results: RA patients have a significant decrease (p<0.05) in CD11c mDC circulating in peripheral blood compared to age matched HC. The expression of CD40 on pDC in RA patients is significantly increased compared to HC (p<0.001). A comparative analysis of mDC in peripheral blood, synovial fluid and synovial tissue highlighted an increase in DC maturation as DC migrate from blood, to fluid and finally tissue. CD40 and CD80 on mDC are significantly increased (p<0.05) in synovial tissue and synovial fluid compared to that of matched peripheral blood. CD141 + DC are a rare DC population within the peripheral blood whose main function is to cross present antigen to CD8 + cytotoxic T cells. The synovial fluid contains a significant increase in the percentage of these CD141 + DC compared to circulating blood (p<0.001). Finally MoDC cultured in the presence of explant conditioned media have an increased percentage of CD83 positive cells and these cells display significantly increased expression of CD80 (p<0.05) compared to basal medium. Conclusions: DC have a more mature and activated phenotype in the synovial tissue compared to that in synovial fluid or peripheral blood. Given that there are also lower circulating levels of DC in RA patients compared to controls our data suggest that peripheral blood DC are recruited to the joint and this unique microenvironment induces a program of DC maturation and activation. Disclosure of Interest: M. Canavan: None declared, M. O'Rourke: None declared, C. Orr: None declared, D. Veale Grant/research support from: Abbvie, MSD, Pfizer, Roche, Consultant for: Pfizer, Roche, Speakers bureau: Abbott, MSD, Pfizer, Roche, U. Fearon: None declared